EFFECTS OF TEMPERATURE ON THE PHOTOSYNTHESIS OF ANTARCTIC FRESHWATER GREEN ALGAE (ABSTRACT) (14th Symposium on Polar Biology) - ナガシマ, ヒデユキ; シミズ, ミキコ; オオタニ, シュウジ; モモセ, ハルオ; NAGASHIMA, Hideyuki; SHIMIZU, Mikiko; OHTANI, Shuji; MOMOSE, Haruo (National Institute of Polar Research, 1993)
P(論文) departmental bulletin paper